Peran Musik dalam Film Score - Dimas Phetorant (Institut Seni Indonesia Denpasar, 2020)
Scores are things that cannot be separated from the film. The score has an important role in the film. Apart from being a communication tool, scores are needed to convey visual messages. The rise of filmmaking lately especially those related to scores requires composers with a variety different disciplines. This paper discusses the score on the film. The method used is observation. The data studied is in the form of journals, books, pictures, videos, which have been described in written form.